The heart of perfection : how the saints taught me to trade my dream of perfect for God's - Campbell, Colleen Carroll, 1974- (Howard Books, 2019)
Spiritual perfectionism<U+2014>an obsession with flawlessness rooted in the belief that we can earn God<U+2019>s love<U+2014>is the most dangerous form of perfectionism because so many of us mistake it for virtue, or deny that it afflicts us at all. Its toxic cycle of pride, sin, shame, blame, and despair distorts our vision, dulls our faith, and leads us to view others through the same hypercritical lens we think God is using to view us. As a lifelong overachiever who drafted her first résumé in sixth grade and spell-checked her high-school boyfriend<U+2019>s love letters, Colleen Carroll Campbell knows something about the perfectionist trap. But it was only after she became a mother that she started to see how insidiously perfectionism had infected her spiritual life, how lethal it could be to her happiness and her family, and how disproportionately it afflicts the people working hardest to serve God. In the ruins of her own perfectionist mistakes, Colleen dug into Scripture and the lives of the canonized saints for answers. She discovered to her surprise that many holy men and women she once saw as encouraging her perfectionism were, in fact, recovering perfectionists. And their grace-fueled victory over this malady<U+2014>not perfectionist striving<U+2014>was the key to their heroic virtue and contagious joy. In The Heart of Perfection, Colleen weaves the stories and wisdom of these saints with Scripture and beautifully crafted tales of her own trial-and-error experiments in applying that wisdom to her life. She introduces us to such saints as Jane de Chantal, a single mother who conquered her impatience only after her ex-perfectionist friend Saint Francis de Sales convinced her to trade punishing prayer regimens for the tougher discipline of showing gentleness to rude in-laws, rowdy kids, and herself. Colleen describes the battle against obsessive guilt that turned timid people-pleaser Alphonsus Liguori into a fearless defender of God<U+2019>s mercy; the discernment rules that helped Ignatius of Loyola overcome crippling discouragement and distraction; the concern for reputation that almost cost the world the radical witness of Francis of Assisi; and the biblical work-life balance that Benedict of Nursia pioneered after years of driving himself and others too hard<U+2014>and without surrendering his holy zeal.